Development and validation of a micellar liquid chromatographic method to determine three antitumorals in plasma. (May 2017) - Romero, Josep Esteve; Chiva, Jaume Albiol; Peris-Vicente, Juan; Ochoa-Aranda, Enrique
Aim: A micellar liquid chromatographic method to determine several anticancer drugs (pazopanib, dabrafenib and regorafenib) in plasma was developed and validated by the guidelines of the EMA.Experimental: Plasma samples were directly injected, after a 1/5-dilution in a micellar solution. The drugs were resolved in <18 min using a C18 column. The mobile phase was an aqueous solution of 0.12 M SDS – 2% 1-pentanol, buffered at pH 7. The detection was performed by absorbance at 260 nm.Results : The values of the main validation parameters were: LOD (0.1–1 mg/l), calibration range (0.2–2 to 80 mg/l), accuracy (-12.5 to +11.7%) and precision (<11.9%).Conclusion: The procedure was conducted by minimum cost, effort, manipulation, time and quantity of hazardous chemicals. The method was useful to determine the drugs at their respective target concentrations, and was found useful for clinical analysis.